A NEW PROCUREMENT METHOD FOR HOUSING PROJECTS IMPLEMENTING IBS MODULAR SYSTEM - Ahmad, Abd Jalil; Mastura, Jaafar; Azlan Raofuddin, Nuruddin; Md Azree, Othuman Mydin (Faculty of Civil Engineering, Universiti Teknologi MARA Pulau Pinang, 2015)
One of the significant contributors to Malaysian gross domestic product is housing projects. To increase the effectiveness of housing project performance, the Malaysian National Housing Policy identified several strategies including Strategic Thrusts 3 and 5 which is through research and development. The adoption of industrialised building system (IBS) has been recognized as one of the steps under this policy but progress has been very slow. Despite government efforts in introducing the IBS Roadmap as long ago as 2003, no detailed IBS building guidelines or standard regulations for procurement systems or contract documents in terms of tendering, design, construction and operations have been produced. A specific procurement system is required as IBS involves special procedures and processes which are different to traditional methods. Previous researches had concluded that the current traditional and modern procurement methods were not suitable for IBS projects especially in terms of project coordination and payment. The only available reference or guidelines for IBS projects are only related to product-based information. Since there is no specific procurement method for IBS projects, many problems on project delivery system have arose thus becoming barriers for IBS adoption. The objective of this paper is to discuss the procurement system which best suits IBS adoption in Malaysian housing projects. From the discussion, it is suggested that a new procurement model should be introduced to ensure the IBS can be efficiently implemented.